Contribution of B cells to cortical damage in multiple sclerosis - Bhargava, Pavan; Hartung, Hans-Peter; Calabresi, Peter A (Brain, 2022)
Multiple sclerosis is associated with lesions not just in the white matter, but also involving the cortex. Cortical involvement has been linked to greater disease severity and hence understanding the factor underlying cortical pathology could help identify new therapeutic strategies for multiple sclerosis. The critical role of B cells in multiple sclerosis has been clarified by multiple pivotal trials of B-cell depletion in people with multiple sclerosis. The presence of B-cell rich areas of meningeal inflammation in multiple sclerosis has been identified at all stages of multiple sclerosis. Leptomeningeal inflammation is associated with greater extent of cortical demyelination and neuronal loss and with greater disease severity. Recent studies have identified several potential mechanisms by which B cells may mediate cortical injury including antibody production, extracellular vesicles containing neurotoxic substances and production of pro-inflammatory cytokines. Additionally, B cells may indirectly mediate cortical damage through effects on T cells, macrophages or microglia. Several animal models replicate the meningeal inflammation and cortical injury noted in people with multiple sclerosis. Studies in these models have identified Bruton's tyrosine kinase inhibition and type II anti-CD20 antibodies as potential agents that can impact meningeal inflammation. Trials of anti-CD20 monoclonal antibodies in people with multiple sclerosis have unsuccessfully attempted to eliminate B cells in the leptomeninges. New strategies to target B cells in multiple sclerosis include Bruton's tyrosine kinase inhibition and cell-based therapies aimed at B cells infected with Epstein-Barr virus. Future studies will clarify the mechanisms by which B cells mediate cortical injury and treatment strategies that can target B cells in the leptomeninges and CNS parenchyma.
Keywords: cortical injury; proteinkinasa BTK; BTK inhibition; anti-CD20; Multiple Sclerosis; leptomeningeal inflammation; cytokiny; Antibodies, Monoclonal; Inflammation; zvířata; virus Epsteinův-Barrové; zánět; B-lymfocyty; infekce virem Epsteina-Barrové; Epstein-Barr Virus Infections; CXCL-13; multiple sclerosis; roztroušená skleróza; Herpesvirus 4, Human; B-Lymphocytes; Cytokines; monoklonální protilátky; Animals; B cell; Agammaglobulinaemia Tyrosine Kinase